AKUNTABILITAS PELAYANAN PUBLIK TERHADAP PENGELOLAAN DANA DESA BULO WATTANG KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Herawati Herawati; Lukman Lukman; Abdul Razak Useng (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the accountability of public services to the management of village funds in the village of Bulo Wattang, Panca Rijang District, Sidenreng Rappang Regency. The population of this study was 360 households using the Slovin formula to obtain a sample of 78 households. The sampling technique used is random sampling. This type of research is quantitative descriptive. Data collection techniques are observation, library research and questionnaires. Data analysis techniques using descriptive analysis, data quality tests (validity and reliability), classic assumption tests, linear regression and hypothesis testing with the help of SPSS 21.0 with a measurement scale using a Likert Scale. The results showed that the accountability of public services affects the management of village funds by 53% while the results of the analysis of village fund management data by 58.55% with a less good category while the relationship of public service accountability with the management of village funds amounted to 0.710 categorized a strong relationship, which in providing public services quality by applying one of the principles of accountable government can increase the success of village fund management.